Influence and verification of different feed ranges on cold pilgering - CHU Zhi-bing; WEI Dong; YANG Yan-long; HUANG Qing-xue; HU Zheng-huan (工程科学学报)
To achieve better performance in finished cold-pilger rolled stainless steel tubes, it is critical to select an appropriate feed range. In this study, cold-rolling 304 stainless steel tube was used as the research object to simulate the entire cold-pilgering process at different feed ranges. Using finite element software, it was comparatively analyzed that the feed range effects on the metal flow rate, rolling force, equivalent stress, residual stress, and piping spring-back. The results indicate that the metal flow rate increases with an increased feed range in the groove bottom and the contact of the groove flank with the roll. In addition, the rolling force, equivalent stress and residual stress increase with increases in the feed range, increments of which will increase the spring-back of the piping. Rolling tests at different feed ranges were performed with the help of experimental rolling mill and it is found that test results are roughly identical to the simulation results. experimental test results regarding the dimensions and residual stress of the piping provide evidence for optimizing the selection of the feed range in pilger rolling.